Implementation of Mamdani Fuzzy Logic Control System on DC Motor Speed Controller - Basilio Mendonca Freitas; Mochammad Rameli; Rusdhianto EAK (Department of Electrical Engineering ITS and FORTEI, 2017)
Abstract— Drive system is an important role important role in industrial processes, especially in electrical control. Maintaining a DC motor speed is a control system task that requires several method. Generally, set-point is defined as point of demand, and its comparation against process value (current speed) resulted in error. Both error and delta-error are two parameters required to the control system to determine system behavior in correction action. Such system of controller is a useful component to suppress the error signal so that the desired performance can be obtained. This research designs system of DC motor rotation speed control using Arduino Uno microcontroller to meet control specification on laboratory scale, implementing control application and Fuzzy Control System as control system algorithm.Because of its ability to be easily modeled using human intuitive, adaptive, does not require complex mathematical equations, not limited to linear or constant systems, and easily adapted to human input, Mamdani Fuzzy Logic Control System is used. Keywords: Mamdani Inference Engine, Fuzzy Logic, Arduino Uno, Rotation Speed Control, DC Motor